2005
DOI: 10.2355/isijinternational.45.1887
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbon Contents in Steels on Alloy Layer Growth during Hot-dip Aluminum Coating

Abstract: Hot-dip aluminum coating of hypo-eutectoid steels containing 0.05-0.88 mass% carbon were performed, and the alloy layers formed in the coating were investigated. In the hot-dip aluminum coating at immersion temperatures ranging from 700 to 850°C, the alloy layers on the steels consisted of a single phase of the intermetallic compound Fe 2 Al 5 . The thickness of the alloy layer increased in proportion to the increasing square root of the immersion time (t 1/2 ) for immersion temperatures lower than 800°C for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Several studies on the reaction layer formed by the reaction of the pure liquid Al with steel (Fe) have already been conducted, in most of which the reaction layer is mainly formed from the θ (FeAl 3 ) and η (Fe 2 Al 5 ) phases. The reported θ phase existed on the liquid Al side, with a thickness much thinner than that of the η phase [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. There have been many studies focusing on the morphology and growth mechanism of the η phase in particular, rather than the θ phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on the reaction layer formed by the reaction of the pure liquid Al with steel (Fe) have already been conducted, in most of which the reaction layer is mainly formed from the θ (FeAl 3 ) and η (Fe 2 Al 5 ) phases. The reported θ phase existed on the liquid Al side, with a thickness much thinner than that of the η phase [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. There have been many studies focusing on the morphology and growth mechanism of the η phase in particular, rather than the θ phase.…”
Section: Introductionmentioning
confidence: 99%
“…The η phase grows toward the solid steel in the form of columnar grains and is known to be tongue-or sawtooth-shaped at the η phase/steel interface [7][8][9][10][11][12][13][14][15][16]. The mechanism of this morphology is due to the high vacancy concentration in the c-axis of the crystal structure (orthorhombic, oC24) of the η phase that causes Al to rapidly diffuse in the (001) direction [7][8][9][10][11][12][13][14][15][16]. It is also reported that the growth of the η phase obeys a parabolic rate law via the diffusion process [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of growth of the Fe-Al intermetallic compounds is dependant on nucleation conditions, chemical reactions, and diffusion coefficient. [29][30][31][32][33][34][35][36][37][38] Denner et al 29) detected the formation of η-Fe2Al5 and θ-FeAl3 compounds in the case of the interaction between liquid aluminum and solid iron during hot dip aluminizing. The parabolic kinetics of growth of the two intermetallic compounds was proposed in references, 30,31) whereas negative deviations from the parabolic relationship was observed after long reaction times between the liquid aluminum saturated with Fe and solid iron.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the Fe 2 Al 5 (η) phase will be formed in a smaller amount than that observed in the phase diagram due to interdiffusion. Studies on the intermetallic compounds formed by the diffusion of Fe and pure Al [10][11][12], Fe and Al alloy [13,14], steel and pure Al [15][16][17][18][19][20][21][22][23][24][25], and steel and Al alloy [26][27][28][29] have been conducted for a long time. The intermetallic compounds formed in these studies were classified into three types: (1) [10][11][12][13][14][15][16][17][18]26,27].…”
Section: Discussionmentioning
confidence: 99%